Cost-effectiveness of osimertinib versus standard EGFR-TKI as first-line treatment for EGFR-mutated advanced non-small-cell lung cancer in China - Shu, Yamin; Ding, Yufeng; He, Xucheng; Liu, Yanxin; Wu, Pan; Zhang, Qilin (Frontiers in Pharmacology, 2022)
Objective: The purpose of this study was to estimate the cost-effectiveness of osimertinib for the first-line treatment of patients with EGFR-mutated advanced non-small-cell lung cancer (NSCLC) from the perspective of Chinese healthcare system. Methods: A Markov model was developed to simulate the outcomes and direct medical costs of osimertinib or standard EGFR-TKI in first-line treatment of patients with previously untreated EGFR-mutated advanced NSCLC. Individual patient survival data were extracted from the FLAURA randomized clinical trial. Clinical costs and utilities input estimates were collected from local hospital and available literatures. Quality-adjusted life-year (QALY), incremental cost-effectiveness ratio (ICER), incremental net monetary benefit (INMB) and incremental net health benefit (INHB) were calculated for the two treatment strategies over a 10-year lifetime horizon. In addition, one-way sensitivity analysis, probabilistic sensitivity analysis and subgroup analysis were performed to test the robustness of the model. Results: On baseline analysis, osimertinib achieved additional 0.39 QALYs and 15,443.78 incremental costs compared with standard EGFR-TKI (gefitinib or erlotinib), which resulted in the ICER of 39,369.53/QALY. The INMB was -755.11, and the INHB was -0.02 QALYs at a WTP threshold of 37,663.26/QALY in China. One-way sensitivity analysis showed that the utility of PFS had the strongest association with the ICER. Osimertinib had approximately 46.4% probability of being cost-effective at the WTP threshold of 37,663.26/QALY. Conclusion: First-line osimertinib therapy might not be cost-effective in China for patients with EGFR-mutated advanced NSCLC compared with standard EGFR-TKI based on its current marketed price. A significant more favorable cost-effectiveness could be achieved when the price of osimertinib was reduced by 5%.